Valvular Heart Diseases in Women: Surgical Outcomes and Gender Differences - Sobia, Farah; Paracha, Vaqar Illahi; ., Tahseen; Ullah, Asad; Ara, Shabnum (Pakistan Armed Forces Medical Journal, 2026)
Objective: To describe the pattern of Valvular Heart Disease (VHD) and evaluate gender-based differences in surgical outcomes among patients undergoing Valvular heart surgery at a tertiary cardiac care center. Study Design: Quasi Experimental study. Place and Duration of Study: Cardiac Surgery Department, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Jan 2023 to Dec 2025. Methodology: Data from 965 patients aged >18 years, of both genders, were retrospectively collected using consecutive sampling. The cohort included individuals who underwent elective or emergency valvular heart surgeries either single or multiple valve repair or replacement, with or without concomitant CABG, performed through conventional or minimally invasive approaches. Those patients whose data were incomplete or missing were not included in the study. Patients were classified by gender for the comparisons in baseline demographics, operative variables, and early postoperative outcomes. Results: Out of the 965 patients, 387(40.1%) were female and 578(59.9%) were male. Males underwent more aortic valve replacements (77.16% vs. 22.8%, p<0.001). However, mitral valve replacements were performed more often on females (61.6% vs. 38.93%, p<0.001). Males had more complex combined procedures, contributing to their longer bypass and cross-clamp times (174 vs. 157 minutes; 128 vs. 112 minutes; p<0.001). Early postoperative mortality was slightly higher in females (3.6%) than in males (2.8%) but difference was insignificant (p>0.05). Conclusion: Gender-based variations were evident in procedural profiles and perioperative characteristics in VHD patients. Recognizing these differences may help optimize preoperative evaluation and tailor surgical strategies to improve overall outcomes.